From Hunter to Protector: The Invention and Reinvention of the Nuri Talaud - Karno Batiran; Micah R. Fisher (Forestry Faculty, Universitas Hasanuddin, 2020)
This article describes the ways in which the Nuri Talaud, a small colorful bird located on an island at the northern reaches of Indonesia, first became a hunted commodity and evolved into a thriving protected species. Told from the life history of Om Zaka, a local hunter turned bird conservationist, this article describes the background that shaped the shifting values placed on the Nuri Talaud. The bird initially gained value as a symbol of the state through its selection for inclusion in Indonesia’s national theme park. As a result of its newfound prominence, local hunters emerged to systematically hunt the bird for sale through a network of international species trade. Nearly facing extinction, various actors and initiatives came together to protect the Nuri Talaud. This paper shows the ways in which a species can be targeted to almost extinction, and the processes that can take shape to ensure its protection.